Transient Permeation Enhancer® (TPE®) technology for oral delivery of octreotide: a technological evaluation. (3rd October 2021) - Brayden, David J.; Maher, Sam
ABSTRACT: Introduction: The FDA approval of oral semaglutide for type 2 diabetes (2019) and oral octreotide for acromegaly (2020) is evidence that selected niche peptides can be administered orally if formulated with selected intestinal permeation enhancers. Areas covered: We evaluated the oral octreotide formulation, MYCAPSSA® (Chiasma Pharmaceuticals, Needham, MA, USA). An outline of the current standard of care in acromegaly and the benefits of oral octreotide versus depot injections is provided. We discuss the Transient Permeation Enhancer (TPE®) technology used and detail the safety and efficacy data from animal models and clinical trials. Expert opinion: TPE® is an oily suspension of octreotide that includes a number of excipients that can transiently alter epithelial barrier integrity by opening of intestinal epithelial tight junctions arising from transcellular perturbation. Phase I studies using 20 mg octreotide capsules yielded a relative oral bioavailability of ~0.7% and primary endpoints were achieved in two Phase III studies. The oral octreotide dose required to achieve these endpoints was over 200 times that of the 0.1 mg immediate-release subcutaneous injection, a reminder of the difficulty in achieving oral absorption of macromolecules. Many acromegaly patients will prefer a convenient twice-daily oral formulation of octreotide compared to monthly depot injections.